Supervisi Akademik dalam Membangun Mutu Pendidikan Islam - Janna, Miftachul; Ashari, M. Yahya (TSAQOFAH, 2026)
Academic supervision plays a strategic role in improving the quality of Islamic education; however, various studies indicate that supervisory practices in madrasah still face challenges, including limited supervisor competence, weak follow-up coaching, and an orientation that tends to be administrative, resulting in suboptimal quality of teaching and learning processes and outcomes. This study aimed to analyze the concept of academic supervision from the perspective of Islamic education, encompassing its definition, objectives, components, and principles, and to examine its contribution to quality improvement. The method used was library research through a systematic review of national scholarly articles published between 2020 and 2025 that are relevant to the theme of academic supervision in Islamic education. Data were analyzed thematically by identifying conceptual patterns and empirical findings in the literature. The results show that academic supervision in Islamic education is understood as a process of continuous professional coaching that includes planning, observation, feedback, and follow-up, with the primary aims of enhancing teacher competence, improving the quality of instruction, and strengthening a professional culture in madrasah. The dominant components of supervision include planning, implementation, evaluation, and coaching, while the prominent principles are objectivity, collaboration, constructiveness, sustainability, and the internalization of Islamic values. The study concludes that there is a positive relationship between systematic academic supervision practices and the improvement of Islamic education quality. Theoretically, this review enriches models of supervision grounded in Islamic values, while practically it provides a foundation for developing more effective and context-sensitive supervisory patterns in madrasah settings, including the need to strengthen supervisor capacity and to formulate standardized operational guidelines for supervision.